Bridgerton : The Viscount Who Loved Me - Book 2 - Quinn, Julia, 1970- (New York, New York : Avon, an imprint of HarperCollinsPublishers, 2021)
"This time the gossip columnists have it wrong. Londons most elusive bachelor Anthony Bridgerton hasnt just decided to marry-hes even chosen a wife! The only obstacle is his intendeds older sister, Kate Sheffield- the most meddlesome woman ever to grace a London ballroom. The spirited schemer is driving Anthony mad with her determination to stop the betrothal, but when he closes his eyes at night, Kates the woman haunting his increasingly erotic dreams...Contrary to popular belief, Kate is quite sure that reformed rakes do not make the best husbands-and Anthony Bridgerton is the most wicked rogue of them all. Kates determined to protect her sister -but she fears her own heart is vulnerable. And when Anthonys lips touch hers, shes suddenly afraid she might not be able to resist the reprehensible rake herself..."-- Publishers description.
"Anthonys story"--Cover.
Keywords: Families -- Fiction; Nobility -- Fiction; Manners and customs -- Fiction; Man-woman relationships -- Fiction; Great Britain -- Social conditions -- 19th century; Fiction; Historical fiction; Romance fiction